Religion and Negative Attitudes towards Homosexuals: An Analysis of Urban Young People and Their Attitudes towards Homosexuality. (August 2015) - Roggemans, Lilith; Spruyt, Bram; Droogenbroeck, Filip Van; Keppens, Gil
Public opinion research has repeatedly shown that religious persons report more prejudice against homosexuality when compared to their non-religious counterparts. This article contributes to a better understanding of this relationship by studying attitudes of youth in two of the three largest cities of Flanders ( N : 1907). The ethnic and religious heterogeneous population of these cities allows us to empirically disentangle the relevance of both religious involvement (strong versus weak) and the specific religious conviction with respect to negative attitudes towards homosexuals. This offers us a more detailed view on the exact nature of the relationship between religiosity and the latter attitudes among youth than what has been achieved so far. For both Christian and Muslim believers, we found more negative attitudes towards homosexuality, even after controlling for authoritarianism and a more traditional view on gender roles. Although boys appeared, in general, more negative towards homosexuality than girls, the gender gap amongst young Muslims was twice as large when compared to non-Muslims.